A CEFR-based Comparison of English and Turkish Language Teaching Course Books in Terms of Speaking and Writing Skills - Demi̇rel, İbrahim Fatih; Fakazli, Özlem (Afyon Kocatepe University, 2021)
This study aims to investigate to what extent the competences in the Common European Framework of Reference for Languages (CEFR) (Council of Europe, 2001) are fulfilled in language teaching course books in terms of productive skills (speaking-writing) in foreign / second language teaching. More specifically, in the study, speaking and writing activities in Headway for teaching English as a foreign/second language and in Yeni İstanbul for teaching Turkish as a foreign/second language, which were said to have been developed based on CEFR, were examined and compared in terms of the compatibility with the competences specified in the CEFR through content analysis. At this point, the distinction of ‘writing / speaking as a production skill’ and ‘writing / speaking as an interaction skill’ defined in the CEFR has been used in the detailed analysis of the activities. According to the content analysis, it was observed that there were differences and similarities in both course books in terms of the implementation of CEFR and the representation of A2 level descriptors. Although both course books claim that they have been developed with reference to the CEFR, findings showed that they do not reach the learning outcomes in terms of speaking and writing skills related to ‘interaction’ and ‘production’ specified in the CEFR at the same rate. Basically, the study concluded that ‘interaction’ skills in Headway and ‘production’ skills in Yeni Istanbul are prioritized. The results also emphasize that these two course books need to be revised and reorganized to reflect the CEFR at A2 level. Bu çalışma, yabancı/ikinci dil öğretiminde anlatma becerileri (konuşma-yazma) açısından, Avrupa Dilleri Ortak Çerçeve Programında (CEFR) yer alan yeterliliklerin dil öğretimi ders kitaplarında ne ölçüde yerine getirildiğini araştırmayı amaçlamaktadır. Bu amaçla, çalışmada yabancı/ikinci dil olarak İngilizce öğretim kitabı Headway ve yabancı/ikinci dil olarak Türkçe öğretim kitabı Yeni İstanbul; konuşma ve yazma etkinliklerinin CEFR yeterlilikleri ile uygunluğu açısından incelenmiş ve karşılaştırılmıştır. Bu noktada CEFR’de yer alan ‘üretim becerisi olarak yazma/konuşma’ ve ‘etkileşim becerisi olarak yazma/konuşma’ ayrımı etkinliklerin detaylı analizinde kullanılmıştır. İçerik analizinin sonucunda CEFR'nin uygulanması ve A2 düzeyi tanımlayıcıların temsili açısından her iki ders kitabında farklılıklar ve benzerlikler olduğu görülmüştür. Bu iki ders kitabının da CEFR referans alınarak geliştirildiği belirtilmesine rağmen, CEFR'de yer alan konuşma ve yazma becerileriyle ilgili öğrenme çıktılarına ‘etkileşim’ ve ‘üretim’ becerileri açısından aynı oranda ulaşamadıkları tespit edilmiştir. Temel olarak Headway’de ‘etkileşim’ becerilerinin; Yeni İstanbul’da ise ‘üretim’ becerilerin öncelendiği görülmüştür. Bulgular, iki ders kitabının da CEFR'yi A2 düzeyinde yansıtmak için revize edilmesi ve yeniden düzenlenmesi gerektiğini vurgulamaktadır.
Keywords: CEFR; foreign/second language teaching course books; speaking skill; writing skill; Alan Eğitimleri; CEFR; Speaking Skill; Writing Skill; Other Fields of Education; Foreign/Second Language Teaching Course Books